Developing Interactive Web-Based Digital Media on Guidance and Counseling Services - Zakiya, Asti putri; Riswandi, Riswandi; Mujiyati, Mujiyati (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Information technology has become an integral part of everyday life. The use of digital media provides various conveniences in accessing information and services, including in the fields of education and counseling guidance.  The application of web page-based digital media with formfacade integration in counseling guidance information services aims to achieve several main objectives. Increasing information accessibility, providing interesting and interactive materials, supporting effective guidance processes and optimizing the use of technology in education. With this, the research method used is the development of the 4D model, by developing webpage-based digital media with formfacade. Based on the results of the design expert test, the results obtained 92% with a very good category, the results of the content expert test obtained 92.5% with a very good category. This means that the product in terms of design and content is very good. So hopefully, the development of this information service can make a positive contribution in helping students explore and develop their potential optimally.